KATA 'SĀFĀR' DALAM PERSPEKTIF SUFI: KAJIAN TERHADAP METAFORA KONSEPTUAL GEORGE LAKOFF - Chaer, Hasanuddin; Rasyad, Abdul; Mari'i, Mari'i; Hidayat, Rahmat; Susanti, Pipit Aprilia; Riyanto, Andra Ade (Universitas Muhammadiyah Surabaya, 2024)
This article delves deeply into the essence of the word 'Sāfār' from a Sufi perspective, utilizing the conceptual metaphor framework developed by George Lakoff. The research aims to uncover the philosophical and spiritual meanings contained within the word 'Sāfār' in the context of Sufi tradition, and how the use of conceptual metaphor can deepen our understanding of Sufi mystical journeys. Within Lakoff's